REVIEWING THE RESULT OF MACHINE TRANSLATION: A CASE FOR INDONESIAN TRANSLATION VERSION BY GOOGLE TRANSLATE AND IMTRANSLATOR - Akhmad Baihaqi; Away Mulyana (PROJECT (Professional Journal of English Education), 2021)
This research is intended to describe the translation version of a literary story that produced by the machine translation. This study used qualitative research. The research was conducted from a literary story of the storybook of Robin Hood: Level 2, retold by Liz Austin. The book was published by Pearson Education Limited in 2000 (the first edition). Research data and analysis were taken from the documentation of the translation results of different machine translation, that is Google Translate and IMTranslator. The result proves that both Google Translate and IMTranslator can help translators to do their works quickly. There are also some weaknesses from those MT as follows: (1) some versions are inaccurate and inappropriate according to the grammatical rules; (2) those MT can only translate on words for word and literal level, so the versions are looked inaccurate and inappropriate for some contexts; (3) those MT also cannot distinguish connotative or associative meanings; and (4) the results of MT serve only as pre-translation, therefore, they still need further discussion and adjustment by the human translators to achieve more acceptable, readable, and understandable results.